SAT0558 New Generation Translocator Protein Pet Tracers To Image Arthritis by Macrophage Targeting in Rheumatoid Arthritis Patients: A Proof of Concept Study. (15th July 2016) - Bruijnen, S.; Gent, Y.; Huisman, M.; Windhorst, A.; Kassiou, M.; Lammertsma, A.; Hoekstra, O.; Voskuyl, A.; Van der Laken, C.
Abstract : Background: Previously, PET and macrophage targeting by translocator protein (TSPO) tracer [ 11 C]-(R)-PK11195 has shown promising value to predict development of RA in the very early arthralgia phase, and flares in clinical remission. Nevertheless, the tracer [ 11 C]-(R)-PK11195 showed rather high peri-articular background uptake which may limit detection of more subtle arthritis activity. In preclinical setting, our group recently showed more favorable imaging characteristics of two new candidate high affinity translocator protein (TSPO) tracers, [ 11 C]DPA-713 and [ 18 F]DPA-714, to visualize arthritis. Objectives: To investigate the imaging potential of [ 11 C]DPA-713 and [ 18 F]DPA-714 as compared to [ 11 C]-(R)-PK11195 for visualization of inflamed joints of RA patients using PET-CT. Methods: RA patients with at least two clinically inflamed hand joints were included. PET-CT scans of their hands were obtained after intravenous injection of [ 18 F]DPA-714, [ 11 C]DPA-713 or [ 11 C]PK11195. Two different tracers were compared per patient, respectively [ 11 C]PK11195 vs. [ 18 F]DPA-714 or [ 18 F]DPA-714 vs. [ 11 C]DPA-713. Quantitative analysis was done by drawing volumes of interest (VOI) over joints with visually elevated tracer uptake and background VOIs were drawn on metacarpal bone. Standardized Uptake Values (SUVs) and target-to-background (T/B) ratios were determined. Data of the tracer [ 18 F]DPA-714 were pooled for analysis. Furthermore, blood was drawn to investigate TSPO receptor polymorphism because a TSPO rs6971 polymorphism is believed to show lower binding affinity (1). Results: Nine RA patients (female3/9; age 54±18; RF+ 7/9; aCCP+ 6/9) were included with a DAS28 of 4.7±1.4 at inclusion. Clear visualization of arthritic joints was obtained with all three tracers. The absolute uptake (SUV) in arthritic joints was comparable for all 3 tracers with a trend of slightly higher uptake of [ 11 C]DPA-713 (Table). However, T/B ratios of both [ 18 F]DPA-714 and [ 11 C]DPA-713 were higher than of [ 11 C]PK11195 respectively almost 2-fold higher of [ 18 F]DPA-714 and 2, 5-fold of [ 11 C]DPA713 (Table). Although the "low binding" TSPO polymorphism rs6971 was present in 3/9 patients, PET outcome was not different from patients without the polymorphism. Conclusions: This is the first study that shows excellent arthritis imaging with both new generation TSPO tracers, [11C]DPA-713 and [18F]DPA-714, in active RA patients. Although imaging outcome was slightly more favorable of [11C]DPA-713, both tracers performed well with higher target-to-background as compared to the previously investigated macrophage tracer [ 11 C]PK11195. The tracers provide opportunities for potential clinical applications of both early diagnosis and therapy monitoring of RA disease activity. References: Zanotti-Fregonara et al., ACS Chem. Neurosci. 2014, 5, 963–971, dx.doi.org/10.1021/cn500138n Disclosure of Interest: None declared